A new adaptive routing algorithm using partitioning scheme in x-Folded TM topology to avoid deadlock. (6th May 2022) - Moudi, Mehrnaz; Othman, Mohamed
A critical issue for interconnection networks is providing the shortest path without deadlock in each topology, and efficient routing algorithms are essential to avoid deadlock. In this paper, a new adaptive routing algorithm in x-Folded TM topology is presented. Using a partitioning scheme and admitting deadlock-free zones are the main factors in producing such an algorithm. The partitioning scheme exposes the relation of this routing to the x-Folded TM topology. To perform extensive simulation experiments, the traffic patterns and a wide range of injection rates are analysed. The simulation results show performance improvements when the performance is mainly dependent on the topology and the applied routing performance in each network. The efficiency of new adaptive routing to avoid deadlock in the x-Folded TM topology has been proven in this paper.